Co-production of Proteases and Bioactive Protein Hydrolysates from Bioprocessing of Feather Meal - Bernardo,Bernardete da Silva (2019)
Abstract: Feather meal conversion through submerged cultivations with Bacillus strains (CL33A, CL14) yielded proteases and protein hydrolysates. After 4-day (CL33A) and 10-day (CL14) cultivations, protease activities reached 461 U/mL; hydrolysates presented antioxidant (radicals-scavenging, 57-77%; Fe2+-chelation, 14-28%; Fe3+-reduction) and antidiabetic (dipeptidyl peptidase-IV inhibition, 49-52%) potentials. The obtained bioproducts present prospective commercial/industrial applications.